2004
DOI: 10.1016/j.virol.2004.03.049
|View full text |Cite
|
Sign up to set email alerts
|

Use of the red fluorescent protein as a marker of Kaposi's sarcoma-associated herpesvirus lytic gene expression

Abstract: A hallmark of all herpesvirus is the ability to exist in either a latent, or lytic, state of replication, enabling the lifelong infection of its host. Kaposi's sarcoma (KS)-associated herpesvirus (KSHV) can efficiently establish a latent infection in a variety of cell types in vitro, making it a valuable model for the study of latency and reactivation. To facilitate the identification of KSHV lytic replication, and allow subsequent experiments with live cells, a recombinant virus, rKSHV.219, was constructed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
452
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 290 publications
(464 citation statements)
references
References 52 publications
8
452
0
1
Order By: Relevance
“…We have previously shown that the fluorescent proteins expressed by rKSHV.219 can be used as indicators of viral entry and infection. As reported before, upon treatment with sodium butyrate the JSC/ rKSHV.219 cell line was able to support viral replication with the release of infectious viral particles (23). The virus yield can easily be determined using a susceptible cell line by evaluating the number of GFP-expressing cells.…”
Section: ␥␦ T Cells Inhibit Hhv-8 Propagation In Vitromentioning
confidence: 70%
See 4 more Smart Citations
“…We have previously shown that the fluorescent proteins expressed by rKSHV.219 can be used as indicators of viral entry and infection. As reported before, upon treatment with sodium butyrate the JSC/ rKSHV.219 cell line was able to support viral replication with the release of infectious viral particles (23). The virus yield can easily be determined using a susceptible cell line by evaluating the number of GFP-expressing cells.…”
Section: ␥␦ T Cells Inhibit Hhv-8 Propagation In Vitromentioning
confidence: 70%
“…C1R, a human lymphoblastoid cell line, was provided by V. Groh (Fred Hutchinson Cancer Research Center). The rKSHV.219 infected JSC-1 cell line (JSC/rKSHV.219) has been described elsewhere (23).…”
Section: Cell Linesmentioning
confidence: 99%
See 3 more Smart Citations